Effects of ketamine hydrochloride (preservative free) and fentanyl citrate added to low dose hyperbaric bupivacaine for sub-arachnoid block in lower uterine caesarian section a comperative study (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Caesarian section is one of the most common operations Now a days for delivery of baby sub-arachnoid block is the better choice. World wide Commonly used bupivacaine with fentanile. Objective The present study was designed to observe the effects of intrathecal ketamine hydrochloride with bupivacaine+complne bupivacaine with fentanyl to observe quality of block eioth duration block during caesarian section. Methods Ninety ASA 1 parturients scheduled for elective caesarian section were randomly selected. There are thirty patients in each group. The base line haemodynamic parameters, heart rate, blood pressure respiratory rate SpO2 and indication of operation were recorded The control group BN (n = 30) received 1.75 ml of 0.5% hyperbaric bupivacaine plus 0.5 ml normal saline intrathecally. While the study group, fentanyl group BF (n = 30) received 1.75 ml of 0.5% hyperbaric bupivacaine plus 0.5 ml (25 mg) injection fentanyl, BK received 1.75 ml of 0.75% hyperbaric bupivacaine plus 0.5 ml (25 mg) of ketamine hydrochloride. Results Duration and quality of sensory and motor block, post-operative analgesia, haemodynamic changes and sedation levels were assessed. There was no significant difference in duration of motor blockade in three groups. Quality of analgesia, sensory block was significant (P